Roots of unity strike again

Algebra Level 4

ω a 1 ω 2 a 1 × ω a 2 ω 2 a 2 × ω a 3 ω 2 a 3 × ω a 4 ω 2 a 4 \frac { \omega-a_1 }{\omega^2-a_1 }\times\frac { \omega-a_2 }{ \omega^2-a_2 }\times \frac { \omega-a_3 }{ \omega^2-a_3 }\times\frac { \omega-a_4 }{ \omega^2-a_4 }

If 1 , a 1 , a 2 , a 3 , a 4 1,a_1,a_2,a_3,a_4 are the 5th roots of unity and ω \omega is a primitive ( ω 1 ) (\omega\neq1) 3rd root of unity, find the value of the expression above.

ω 2 \omega^2 ω \omega 1

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Chew-Seong Cheong
Sep 21, 2015

( ω a 1 ) ( ω a 2 ) ( ω a 3 ) ( ω a 4 ) ( ω 2 a 1 ) ( ω 2 a 2 ) ( ω 2 a 3 ) ( ω 2 a 4 ) = ( ω 2 1 ) ( ω 1 ) ( ω a 1 ) ( ω a 2 ) ( ω a 3 ) ( ω a 4 ) ( ω 1 ) ( ω 2 1 ) ( ω 2 a 1 ) ( ω 2 a 2 ) ( ω 2 a 3 ) ( ω 2 a 4 ) = ( ω 2 1 ) ( ω 5 1 ) ( ω 1 ) ( ω 10 1 ) 1 , a 1 , a 2 , a 3 , a 4 , fifth roots of unity. = ( ω 2 1 ) ( ω 2 1 ) ( ω 1 ) ( ω 1 ) ω 3 = 1 = ( ω + 1 ) ( ω + 1 ) ω 2 1 = ( ω + 1 ) ( ω 1 ) = ω 2 + 2 ω + 1 ω 2 + ω + 1 = 0 = ω \begin{aligned} \frac{(\omega - a_1)(\omega - a_2)(\omega - a_3)(\omega - a_4)}{(\omega^2 - a_1)(\omega^2 - a_2)(\omega^2 - a_3)(\omega^2 - a_4)} & = \frac{(\omega^2 - 1) \color{#3D99F6}{(\omega - 1)(\omega - a_1)(\omega - a_2)(\omega - a_3)(\omega - a_4)}}{(\omega - 1) \color{#3D99F6}{(\omega^2 - 1)(\omega^2 - a_1)(\omega^2 - a_2)(\omega^2 - a_3)(\omega^2 - a_4)}} \\ & = \frac{(\omega^2 - 1) \color{#3D99F6}{(\omega^5 - 1)}}{(\omega - 1) \color{#3D99F6}{(\omega^{10} - 1)}} \quad \quad \small \color{#3D99F6}{1, a_1, a_2, a_3, a_4, \text{ fifth roots of unity.}} \\ & = \frac{(\omega^2 - 1)(\omega^2 - 1)}{(\omega - 1)(\omega - 1)} \quad \quad \small \color{#3D99F6} {\omega^3 = 1} \\ & = (\omega+1)(\omega +1 ) \quad \quad \quad \color{#3D99F6}{\omega^2-1=(\omega+1)(\omega-1)} \\ & = \omega^2 + 2\omega + 1 \quad \quad \quad \quad \color{#3D99F6}{\omega^2 + \omega+1 = 0} \\ & = \boxed{\omega} \end{aligned}

Alan Yan
Sep 22, 2015

( z a 1 ) ( z a 2 ) ( z a 3 ) ( z a 4 ) = z 4 + z 3 + z 2 + z + 1 (z - a_1)(z - a_2)(z - a_3)(z - a_4) = z^4 + z^3 + z^2 + z + 1

You know that ω 3 = 1 \omega^3 = 1 ω 2 + ω + 1 = 0 \omega^2 + \omega + 1 = 0

( ω a 1 ) ( ω a 2 ) ( ω a 3 ) ( ω a 4 ) ( ω 2 a 1 ) ( ω 2 a 2 ) ( ω 2 a 3 ) ( ω 2 a 4 ) = ω 4 + ω 3 + ω 2 + ω + 1 ω 8 + ω 6 + ω 4 + ω 2 + 1 \frac{(\omega - a_1)(\omega - a_2)(\omega - a_3)(\omega- a_4)}{(\omega^2 - a_1)(\omega^2 - a_2)(\omega^2 - a_3)(\omega^2- a_4)} = \frac{\omega^4 + \omega^3 + \omega^2 + \omega + 1}{\omega^8 + \omega^6 + \omega^4 + \omega^2 + 1}

= ω + ω ( ω 2 + ω + 1 ) + 1 ω 2 + 1 + ( ω + ω 2 + 1 ) = ω + 1 ω 2 + 1 ω ω = ω ( ω + 1 ) 1 + ω = ω = \frac{\omega + \omega(\omega^2+\omega+1) + 1}{\omega^2 + 1 + (\omega + \omega^2 + 1)} = \frac{\omega+1}{\omega^2 + 1} \cdot \frac{\omega}{\omega} = \frac{\omega(\omega + 1)}{1 + \omega} = \boxed{\omega}

Lu Chee Ket
Oct 17, 2015

Excel method allows one to see exact orientations of triangle and pentagon:

w = -0.5+0.866025403784439i

w^2 = -0.5-0.866025403784438i

a1 = 0.309016994374947+0.951056516295154i

a2 = -0.809016994374947+0.587785252292473i

a3 = -0.809016994374948-0.587785252292473i

a4 = 0.309016994374947-0.951056516295154i

F1 = 0.204488531107294-0.354184525442962i

F2 = -0.13988638801609+0.242290331331161i

F3 = -1.78716459510874+3.09545988021662i

F4 = 1.22256245201755-2.11754028232038i

P = -0.5+0.866025403784439i

P = w TRUE

Chance of making mistake is lowest.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...